MicroRNA-195 as a prognostic factor for cancer survival outcome in China: a meta-analysis - Wang N; Cao Y; Ge X; Nie J; Yu Y; Li Q; Wang F; Miao L (Cancer Management and Research, 2019)
Ni Wang,1,* Yang Cao,2,* Xianxiu Ge,1,* Junjie Nie,1 Yang Yu,1 Quanpeng Li,1 Fei Wang,1 Lin Miao11Medical Center for Digestive Diseases, Second Affiliated Hospital, Nanjing Medical University, Nanjing, Jiangsu Province, People’s Republic of China; 2Department of General Surgery, The Second Affiliated Hospital of Nanjing Medical University, Nanjing, Jiangsu Province, People’s Republic of ChinaCorrespondence: Lin MiaoDepartment of Gastroenterology, The Second Affiliated Hospital of Nanjing Medical University, 121 Jiangjiayuan, Nanjing, Jiangsu Province 210011, People’s Republic of ChinaEmail linmiao@njmu.edu.cn*These authors contributed equally to this workPurpose: MicroRNA-195 is dysregulated in different kinds of cancers and plays a pivotal role in tumorigenesis. It may function as a prognostic biomarker for cancers. However, the results from articles were not consistent. This study was designed to validate the prognostic value of microRNA-195 in human tumors.Methods: We conducted a detailed search on PubMed until December 31, 2018. The quality of these publications was assessed on the basis of a list of key reviews presented by PRISMA statement. The pooled hazard ratios (HR) and pooled odds ratios (OR) of each 95% confidence interval (95% CI) were calculated to assess the effect.Results: This meta-analysis included 12 studies involving 940 cancer patients to assess the prognostic value of miR-195 in different solid tumors. The results showed that patients with high expression of miR-195 had favorable tumor-node-metastasis (late vs early: pooled OR =0.16, 95% CI: 0.11–0.22, P<0.001), lymph node metastasis (pooled OR =0.25, 95% CI: 0.18–0.35, P<0.001) and distant metastasis (pooled OR =0.26, 95% CI: 0.13–0.52, P<0.001). At the same time, high levels of miR-195 expression were closely correlated with better overall survival (pooled HR =0.46, 95% CI: 0.36–0.58, P<0.001).Conclusion: Elevated microRNA-195 may serve as a potential biomarker to predict a favorable prognosis for various cancer types in China.Keywords: biomarker, prognosis, microRNA-195, expression, meta-analysis